Note on Kurzia (Kurzia) latissima (Kurz, 1875) (Branchiopoda: Anomopoda: Chydoridae) from India - Padhye, Sameer M.; Damme, Kay Van (Zootaxa, 2015)
Members of the chydorid genus Kurzia Dybowski & Grochowski, 1894 (Branchiopoda: Anomopoda) are typically known from the Holarctic and the Neotropics (Rajapaska & Fernando 1986; Hudec 2000; Elmoor-Loureiro 2002; Kotov, 2004). One representative of the sub genus Kurzia, Kurzia (Kurzia) latissima (Kurz 1875) has been reported from India, in the Oriental Zone. These reports either have unreliable or no illustrations (Rane, 1983; Michael & Sharma 1988; Padhye & Dumont 2015). Recently, Chatterjee et al. (2013) have stated that records of K. latissima from India appear morphologically similar to K. latissima s.str. but have not elaborated on it. The aim of this correspondence is to present an initial diagnosis and provide illustrations of a Kurzia latissima-like population from the Northern Western Ghats, Maharashtra Province, India, along with comments on its distribution.